Analysis of periodontal status using laser doppler flowmetry in patients with various types of occlusion and periodontal condition - Ищенко, П. В.; Борисенко, А. В.; Ищенко, Т. Н.; Махнёва, А. В. (Actual Dentistry, 2020)
Relevance. The study of blood flow using laser Doppler flowmetry (LDF) is increasingly used in the analysis of the state of periodontal tissues and blood vessels. This makes it possible to analyze the blood flow in the norm and with structural features of organs and systems, with inflammation in the tissues in the area of interest to us. Material and methods. The study involved 120 people who were somatically healthy and with an intact dentition: 30 people had an orthognathic bite; 30 people had bipognathia; 30 people had progeny and 30 people had a deep bite. And also 30 people with biprognathy – the stabilized periodontal period; 30 people with progenia – the stabilized periodontal period; 30 people with a deep bite and the stabilized periodontal period. Goal. Using LDF, analyze the blood flow velocity in an intact periodontium during orthognathy, as well as in occlusion pathology, and compare the results in occlusion pathology in a stabilized periodontium. Results. When analyzing the results of the study, regularities were revealed: in patients with an intact periodontium during bipognathia and progeny, the microcirculation index was noticeably reduced, which was accompanied by a decrease in the smooth muscle apparatus of the vessel wall and the pressure gradient between arterioles and venules. All this is due to a decrease in the functional load on the periodontium. When the destabilization processes are attached to these pathologies, the activity of the smooth muscle apparatus of the vessel wall and the pressure gradient between arterioles and venules increase, which accordingly affects the increase in microcirculation. Conclusions. The obtained LDF data for biprognathia, progenia, and deep bites have several common features. There is a clear tendency to change both the microcirculation index and the amplitude a, P, y waves / PM * 100 % in the jaw areas with occlusion disorders. With healthy periodontal disease, in the above areas, there is a decrease in microcirculation and the concentration of endothelial cells in the vessel wall. When comparing fragments of an intact and treated periodontium in the form of generalized periodontitis in the stabilization stage in the above areas with occlusion disorders, an increase in the microcirculation index and the values of diagnostically valuable indicators are noted. Key words: LDF, occlusion pathology, stabilized periodontium.